Effectiveness and Safety of Biodegradable Calcium Sulfate Antibiotic Beads as Adjuvant Therapy in Vascular Graft Infections. (4th January 2021) - Doub, James B; Bork, Jacqueline T; Heil, Emily; Stafford, Kristen; Banoub, Mary; Karwowski, John K; Toursavadkohi, Shahab
Abstract: This is a retrospective cohort study evaluating the safety and effectiveness of biodegradable calcium sulfate antibiotic beads in vascular graft infections compared with standard of care. No differences in acute kidney injury or hypercalcemia were observed between the cohorts. Recurrence of infection did not occur in the 13-patient bead cohort compared with 14 patients who had recurrence in the 45-patient nonbead cohort with a number needed to treat of 4.0.